Follow‐up of the re‐evaluation of polyglycerol esters of fatty acids (E 475) as a food additive. (16th May 2022) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Gundert‐Remy, Ursula; Gürtler, Rainer; Husøy, Trine; Manco, Melania; Mennes, Wim; et al.
Abstract: Polyglycerol esters of fatty acids (PEFA, E 475) was re‐evaluated in 2017 by the former EFSA Panel on Food Additives and Nutrient sources added to Food (ANS). As a follow‐up to this assessment, in this opinion, the Panel on Food Additives and Flavouring (FAF) addresses the data gaps identified to support an amendment of the EU specifications for E 475. The Panel performed a risk assessment of undesirable impurities and constituents potentially present in E 475. The Panel concluded that the maximum limits in the EU specifications for the 4 toxic elements (arsenic, lead, mercury and cadmium) should be lowered based on actual levels in the commercial food additive E 475. The Panel also concluded that maximum limits for erucic acid, 3‐monochloropropanediol and glycidyl esters should be included in the EU specifications for E 475. Alternatively, the Panel recommends an amendment of the definition of E 475 to include a requirement that the fats and oils used in the manufacturing of E 475 comply with the respective EU legislation regarding suitability for human consumption. Further, the Panel concluded that there is no need for setting a specification limit for the content of trans ‐fatty acids in E 475 as a limit is established in the Regulation (EU) No 2019/649, i.e. 2 g of trans ‐fat per 100 g fat in food for the final consumer. Finally, the Panel recommends a modification of the definition of E 475 indicating that polyglycerol used for the manufacturing of E 475 should be produced from glycerol meeting the specifications for E 422 (Commission Regulation (EU) No 231/2012). In this case, respective specification limits for epichlorohydrin, acrolein and butanetriol would not be needed for E 475.